Story Repetition in Qur’an as an Islamic Education Learning Strategy (EDUKASIA, 2020)
Qur’an is the main source of Islamic Education or Pendidikan Agama Islam (PAI) teaching materials. In the Qur'an, there are various stories repetitions that are presented well. Repeating the story allegedly has a close relationship with Islamic education learning strategy. The purpose of this study is to provide an understanding that the repetition of stories in the Qur'an can be used as a learning strategy for Islamic religious material. This library research used qualitative data. The data is in the form of primary sources, such as ‘Psikologi Kisah dalam Al-Qur’an’ book The data that had been tested were then analyzed using the content analysis approach of repetition story as PAI learning strategy. The results showed that the concept of stories repetition in the Qur’an is very relevant to be used as PAI learning strategy. The results of the study showed that the story repetition concept in the Qur'an is very relevant to the Islamic education learning strategy. These stories become part of an effective and efficient learning strategy in equipping students with various Islamic studies. The repetition taught by Allah in the Qur'an and prophet in Hadith is one of learning principles. The principle of repetition in learning should be implemented in the Islamic education. So, all methods applied in learning must use repetition.